THE MEDIATING ROLE OF IMPULSE BUYING IN TRANSLATING LIVE MARKETING AND MATERIALISTIC VALUES INTO TIKTOK PURCHASE INTENTIONS - Barusman, Andala Rama Putra; Suryana, Marceilla (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
TikTok Live Shopping has revolutionized social commerce, yet the joint impact of external marketing and internal values on consumer intentions remains under-explored. This study examines the role of social media marketing (SMM) and materialism in driving TikTok Live Shopping purchase intentions, mediated by impulse buying. Utilizing a quantitative, cross-sectional design, data were collected via questionnaires from 143 business students selected through simple random sampling. Structural Equation Modeling (SEM-PLS) was employed to test the hypotheses. The structural model reveals that SMM (β=0.385) and materialism (β=0.356) significantly trigger impulse buying. Furthermore, impulse buying exerts the strongest direct impact on purchase intention (β=0.412) and successfully mediates both SMM (β=0.159) and materialism (β=0.147) pathways. Unlike traditional static e-commerce studies, this research offers novelty by integrating the Stimulus-Organism-Response (S-O-R) framework to demonstrate how real-time, high-FOMO digital marketing interacts with internal psychological traits to accelerate impulse-driven transactions. Practically, social commerce managers must transition from passive broadcasting to interactive, relationship-driven hosting. Theoretically, the study warns that modern social commerce platforms can exploit materialistic vulnerabilities, highlighting the urgent need for consumer digital well-being education.